Conventional and Molecular Studies of Brown Planthopper (Nilaparvata lugens Stal) Resistance Genes in Rice: A Basis for Future Study of Natural Insect Resistance Genes Using Molecular Markers in Nepal - Sharma, Prem N.; Mori, Naoki; Takumi, Shigeo; Nakamura, Chiharu (Nepal Journal of Science and Technology, 2015)
Rice productivity is greatly affected by various biotic and abiotic stresses. Insect-pests are one of the major bioticconstraints to cause significant losses in rice production. Brown planthopper (BPH), Nilaparvata lugens Stål, isthe most serious insect-pest of rice in Asia where most of the world rice is produced. Controlling insects usingchemicals is already proven detrimental not only to environment but also to human health. Integrated PestManagement (IPM) is the best approach to control insect pests. Host plant resistance is the principal componentof IPM along with biological, cultural and physical methods. Use of varietal resistance is the best option to controlBPH. Many BPH resistant rice varieties with natural BPH resistance have been developed and widely used againstBPH. However, frequent breakdown of monogenic resistance by new BPH biotypes has been a serious threat tocontrol BPH. To overcome such difficulty in the use of monogenic resistance, development of durable resistanceis needed as the sustainable means to control BPH. To develop durable resistance, pyramiding of BPH resistancegenes and quantitative trait loci (QTLs), through marker-assisted method, is needed. For this, many BPH resistancegenes and QTLs have already been identified and mapped on rice chromosomes. This article reviews identification,mapping and pyramiding toward successful cloning of BPH resistance genes/QTLs and provides the basis/guidelines to work on natural insect resistance genes using molecular markers in Nepal. DOI: http://dx.doi.org/10.3126/njst.v15i1.12032 Nepal Journal of Science and Technology Vol. 15, No.1 (2014) 145-156